The Implementation of Marketing 4.0 and Augmented Reality Technology in Enhancing Purchase Intention in the East Java Tourism Sector - Meidinda Rachmawati; Alfira Rosadian (STIEKOP MALANG PRESS, 2026)
Purpose – This study aims to investigate the integrated impact of Marketing 4.0 strategies and Augmented Reality (AR) technology application on tourist purchase intention in East Java, Indonesia. Specifically, the study examines the influence of Marketing 4.0 and AR technology on tourist attitudes and purchase intention, as well as the mediating role of AR technology in the relationship between Marketing 4.0 and tourist attitude. Design/methodology/approach – This study employed a quantitative explanatory research design. Data were collected through an online questionnaire distributed to 350 domestic tourists who had visited or planned to visit major tourism destinations in East Java, Indonesia. The collected data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine the direct and indirect relationships among Marketing 4.0, AR technology, tourist attitude, and purchase intention. Findings – The findings demonstrate that Marketing 4.0, characterized by digital interaction and co-creation, has a significant positive influence on tourist attitudes. The perceived usefulness and enjoyment of AR technology also significantly and positively influence tourist attitudes. Furthermore, tourist attitude has a strong positive effect on purchase intention. The results also confirm that AR technology plays a mediating role in the relationship between Marketing 4.0 and tourist attitude. These findings indicate that integrating human-centric digital marketing with immersive AR technology can create more engaging tourist experiences and strengthen tourists' purchase intentions. Research limitations/implications – This study is limited to domestic tourists who have visited or planned to visit major destinations in East Java, Indonesia, which may limit the generalizability of the findings to international tourists or tourism destinations in other regions. The use of cross-sectional data also limits the ability to capture changes in tourist perceptions and purchase intentions over time. Future research could examine international tourists, compare different tourism destinations, and employ longitudinal or experimental approaches to evaluate the long-term effects of AR-based marketing. Originality/value – This study contributes to the tourism marketing literature by integrating Marketing 4.0 and Augmented Reality technology within a unified framework to explain tourist purchase intention. Its originality lies in demonstrating the complementary role of human-centric digital marketing and immersive technology in shaping tourist attitudes and behavioral intentions.